(untitled) (Biological Sciences - PJSIR, 2016)
Bacteriocin producing bacteria are commonly found in meat products to enhance their shelf-life. In the present study, bacterial species were isolated from meat samples (beef) from different localities of Lahore, Pakistan. MRS agar medium was used to isolate lactic acid bacteria (LAB) through spread and streak methods (incubated for 72 h at 37 °C). Identification of bacteriocinogenic LAB strains was done by using staining techniques, morphology based characteristics and biochemical tests. These strains were BSH 1b, BSH 3a, BIP 4a, BIP 3a, BIP 1b and BRR 3a. Antibacterial activity of LAB was performed against food borne pathogens viz., Escherichia coli and Staphylococcus aureus through paper disc diffusion method. Three bacterial strains showed maximum inhibition and characterised by ribotyping viz., BIP 4a was identified as Lactobacillus curvatus, BIP 3a was Staphylococcus warneri and BIP 1b was Lactobacillus graminis. Optimum pH 5-6.5 and 30-37 °C temperature for isolated bacterial strains was recorded. Protein concentration measured was 0.07 mg/mL for BSH 1b, 0.065 mg/mL for BSH 3a, 0.057 mg/mL for BIP 4a, 0.062 mg/mL for BIP 1b, 0.065 mg/mL for BIP 3a and for BRR 3a 0.078 mg/mL, respectively. Bacteriocin of all isolates except BIP 3a was found to be sensitive towards pepsin and resistant towards Rnase. Bacteriocin production was stable at between pH 5.0 and 6.0 and resistant temperature was 40 °C. It was concluded that lactic acid bacteria (LAB) from meat can be helpful as antibacterial agents against food-borne bacterial pathogens because of thermostable producing bacteriocin.